The Concept of Mental Health in Islamic Education: An Integrative Analysis between Positive Psychology and Qur’anic Spirituality - Ahmad Syaipul Bahri (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2026)
This study examines the concept of mental health within the framework of Islamic education by integrating insights from positive psychology and Qur’anic spirituality. The main reason for this research stems from the growing mental health crisis among youth worldwide and the need for holistic frameworks that combine psychological science with spiritual wisdom. Using a qualitative library research approach, the study systematically analyzes classical Islamic texts, modern psychological theories, and contemporary scholarly works to construct an integrative conceptual model. The analysis reveals that Islam views mental health as a dynamic harmony between intellect, emotion, and spirit, anchored in the Qur’anic notions of tazkiyah al-nafs (self-purification). This contrasts yet complements the human flourishing model of positive psychology, which focuses on meaning, engagement, and accomplishment. The findings suggest that Islamic education offers a transformative pedagogical approach that fosters resilience, gratitude, and spiritual awareness, thus providing an ethical-spiritual foundation for mental well-being. The implications of this study emphasize the need for educational institutions to incorporate Qur’anic spirituality and moral development into mental health education, promoting a balance between psychological growth and divine consciousness.